Conditioning services in elite Spanish water polo clubs - Reverter-Masia, J.; Jove-Deltell, C.; Legaz Arrese, A.; Munguia-Izquierdo, D. (Journal of Physical Education and Sport, 2012)
The aim of this research was to determine the conditioning services available to male and female Spanish top division league water polo teams. Our research was based on information obtained from a survey conducted on fitness coaches with a survey response rate of 91.6% (22 of 24 agreed to participate in our research). The survey groups were divided into two categories: group "A" and group "B", the former being that showing the best performance. This superiority may derive from the fact that a high percentage of group A water polo teams had a physical conditioning coach (PCC) with optimal academic and federate training. However, only a low percentage of PCCs had higher academic education or consulted scientific journals. Also, only 9% of them did not report on any work-related deficiencies but rather included deficiencies related to strength training material, fitness evaluation experts and training facilities. Group B teams reported significant deficiencies in almost all the variables within the training environment which, in turn, indicated the existence of significant deficiencies in conditioning practices that coaches offered their players. The study concluded that the fitness levels of teams could be substantially improved by means of better PCCs` academic profiles, training promotion and training environment.